2009
DOI: 10.5005/jcdp-10-4-75
|View full text |Cite
|
Sign up to set email alerts
|

Teething Problems and Parental Beliefs in Nigeria

Abstract: Aim:To determine signs and symptoms associated with teething, parental beliefs about teething, and the effects of socioeconomic status on teething in Nigerian children. Methods and Materials:A cross-sectional study consisting of 1,013 mothers of children between the ages four to 36 months who visited the immunization clinics at the Community Health Centres in Ife Central and Ife East Local Government Areas. Data was analyzed using STATA (Intercooled release 9) for Windows. Results:A total of 765 mothers (75.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
1
14
1
2
Order By: Relevance
“…An urge to bite (93.1%), fever (87.0%), and diarrhea (83%) were the most common signs and symptoms reported by Saudi parents 6 . Contrary to our findings, fever (51.8%), diarrhea (12.5%), and vomiting (2.9%) were the most commonly reported signs and symptoms by Nigerian mothers 10 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An urge to bite (93.1%), fever (87.0%), and diarrhea (83%) were the most common signs and symptoms reported by Saudi parents 6 . Contrary to our findings, fever (51.8%), diarrhea (12.5%), and vomiting (2.9%) were the most commonly reported signs and symptoms by Nigerian mothers 10 .…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, there was no association between the child's sex and systemic signs and symptoms reported by the mother. This is consistent with the findings of Oziegbe et al 10 , who also found no significant relationship between the child's sex and signs and symptoms noticed by the mother 9 . Also, a study in Ethio-pia reported that 91.6% of the mothers believed that teething was associated with various symptoms, such as diarrhea (90.7%) 11 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Esses estudos foram realizados com amostras maiores, e apesar de também apresentarem baixo nível de evidência científica devido à subjetividade e à natureza transversal das pesquisas, assim como observado nos estudos baseados na opinião dos pediatras e odontopediatras, as manifestações mais relatadas foram diarreia e irritabilidade. A irritação ou coceira gengival foi o sintoma mais relatado pelas mães, com mais de noventa por cento dos relatos em alguns estudos 16,20 . A febre também foi um evento bastante citado nessas pesquisas.…”
Section: Resultsunclassified
“…É importante observar a discrepância nos resultados dos estudos de Cunha et al 16 e de Owais, Zawaideh, Bataineh 19 , realizados no Brasil e Jordânia, respectivamente. Ambos os estudos foram realizados com grandes números amostrais, entretanto, enquanto no estudo brasileiro 95% das mães relataram ter observado irritação gengival nas crianças, no estudo da Jordânia, mais da metade das mães não relataram nenhum sintoma relacionado à erupção dentária.…”
Section: Resultsunclassified